2017
DOI: 10.1177/0009922817706143
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injuries Associated With Hoverboard Use in Children

Abstract: Hoverboards burst onto the scene with wide popularity only to be quickly deemed unsafe and banned in many arenas. We conducted a retrospective cohort study of 35 patients seen in our outpatient pediatric orthopedic office over a 1-year period. The mean age of injured patients was 11.14 years; 18 patients were male (51.4%), and 17 were female (48.5%). The highest number of injuries occurred in children 10 to 14 years old who had 57.1% of the injuries. There were a total of 31 fractures in 27 patients. Most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…The literature to date is devoid of multi-center or multi-region investigations of pediatric orthopedic hoverboard–related injuries in the USA. This multi-center study substantiates some of the findings and conclusions drawn in previous single-center or single-region studies in children: hoverboards have created a significant burden of injury, particularly upper-extremity fractures from falls [2, 6, 9, 12, 13, 1618, 20]. All report a significant deficit in the use and regulation of protective gear.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The literature to date is devoid of multi-center or multi-region investigations of pediatric orthopedic hoverboard–related injuries in the USA. This multi-center study substantiates some of the findings and conclusions drawn in previous single-center or single-region studies in children: hoverboards have created a significant burden of injury, particularly upper-extremity fractures from falls [2, 6, 9, 12, 13, 1618, 20]. All report a significant deficit in the use and regulation of protective gear.…”
Section: Discussionsupporting
confidence: 83%
“…It requires a keen sense of balance and control and poses significant risk of forward, backward, and torsional falls, as well as a risk of fingers and toes catching in the wheels. As a result, the hoverboard has been associated since its release with various orthopedic injuries, particularly in children, including upper-extremity fractures related to falls [2, 6, 9, 12, 13, 17, 18, 20] and non-orthopedic injuries, such as concussions and burns (the devices presented a fire hazard). Around the December 2015 holiday season, many social media and news outlets reported injuries related to hoverboards.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the site of the injury, the upper extremity was the most common region of the body to be affected, and the fracture was the most common type of injury. These ndings were replicated by other studies [4,11,12,14,16,28]. Some of these studies also detailed an increase in the wrist and forearm injuries, speci cally fractures.…”
Section: Discussionsupporting
confidence: 52%
“…13 Additionally, Monteilh reported that among a retrospective cohort of 35 pediatric patients <18 years of age with associated electric hoverboard injuries, the upper extremity was the most common fracture location. 14 Furthermore, this study reported that over 85% of e-scooter related injuries were due to ground level fall/crash. This can be explained by the fact that the most common injury mechanism is from falling off the scooter and causing an outstretched hand.…”
Section: Discussionmentioning
confidence: 94%